Patient‐reported convenience of once‐daily versus three‐times‐daily dosing during long‐term studies of pramipexole in early and advanced Parkinson's disease. Issue 1 (27th April 2012) - Schapira, A. H. V.; Barone, P.; Hauser, R. A.; Mizuno, Y.; Rascol, O.; Busse, M.; Debieuvre, C.; Fraessdorf, M.; Poewe, W.; ,
<x xml:space="preserve">Abstract</x> Background and purpose: In chronic diseases including Parkinson's disease (PD), complex pharmacotherapy dosing schedules are reported to reduce adherence, perhaps leading to less‐effective symptom control and, in PD, more erratic stimulation of dopamine receptors. However, blinded clinical‐trial designs preclude direct comparisons of adherence to various schedules. Methods: In two double‐blind (DB) studies of early PD and one of advanced PD, subjects received three‐times‐daily (t.i.d.) pramipexole or placebo. In open‐label (OL) extensions, subjects took extended‐release, once‐daily (q.d.) pramipexole. At 24 or 32 OL weeks, q.d. versus t.i.d. dosing preference was surveyed by questionnaire. Results: Of 590 DB‐trial completers with early PD, 511 entered the OL extension. Of 374 survey respondents, 94.4% preferred q.d. dosing (72.2% of them found it 'very much more convenient' and 27.8%'more convenient'), 2.7% preferred t.i.d., and 2.9% chose 'no difference'. Of 465 DB‐trial completers with advanced PD, 391 entered its OL extension. Of 334 survey respondents, 88.9% preferred q.d. dosing (59.9% of them found it 'very much more convenient' and 40.1%'more convenient'), 5.7% preferred t.i.d., and 5.4% chose 'no difference'. Results excluding DB‐placebo recipients were highly similar. Conclusions: In this first direct comparison of patient preference for q.d. versus t.i.d. dopamine‐agonist dosing, patients with early or advanced PD had a strong preference for q.d. rather than t.i.d. pramipexole. The high proportion of advanced‐PD patients declaring this preference indicates that it does not depend on whether a patient is taking concomitant PD medications dosed more frequently than q.d.